Binaural advantages in sound temporal information processing by neurons in the rat inferior colliculus - Li, Yan; Zhang, Jiping (Frontiers in Neuroscience, 2023)
Previous studies on the advantages of binaural hearing have long been focused on sound localization and spatial stream segregation. The binaural advantages have also been observed in speech perception in reverberation. Both human speech and animal vocalizations contain temporal features that are critical for speech perception and animal communication. However, whether there are binaural advantages for sound temporal information processing in the central auditory system has not been elucidated. Gap detection threshold (GDT), the ability to detect the shortest silent interval in a sound, has been widely used to measure the auditory temporal resolution. In the present study, we determined GDTs of rat inferior collicular neurons under both monaural and binaural hearing conditions. We found that majority of the inferior collicular neurons in adult rats exhibited binaural advantages in gap detection, i.e., better neural gap detection ability in binaural hearing conditions compared to monaural hearing condition. However, this binaural advantage in sound temporal information processing was not significant in the inferior collicular neurons of P14-21 and P22-30 rats. Additionally, we also observed age-related changes in neural temporal acuity in the rat inferior colliculus. These results demonstrate a new advantage of binaural hearing (i.e., binaural advantage in temporal processing) in the central auditory system in addition to sound localization and spatial stream segregation.